Industrial diversity and innovation spillovers: dynamic innovation and adoption - Philip Amison; David Bailey (WWWforEurope, 2013)
This paper explores the links between open innovation and the emergence of a phoenix industry – the low carbon vehicles sector - in the UK's traditional automotive heartland, focusing on the West Midlands region. It highlights three major factors in driving the development of this `phoenix' industry at a regional level. Firstly, it highlights the role of `open innovation' approaches in driving the sector, for example noting that smaller firms can sometimes innovate more quickly/more cheaply than the major auto firms; the increased interaction across technologies, up and down supply chains and between larger and smaller firms. In so doing, it also notes the role of hybrid firms providing services, plus prototyping/low volume manufacturing (largely in niche vehicles) and the transferability of these competences across industrial sectors. Secondly, it points to the role of historic (and relatively immobile) investments in the region, for example the past/ongoing importance of established mass producers, the depth of skills and experience in suppliers and in the local workforce; and cross-overs with the overlapping motorsport cluster. Finally, it stresses the role of public-private sector cooperation, such as: the establishment of the Automotive Council UK and its work in developing technology roadmaps, informing regulation, and supporting development of the UK supply chain (a type of industrial policy as a discovery process and in line with `smart specialisation' principles); the R&D funding programmes developed with industry input; and the earlier role of the Regional Development Agency. Overall, it points to the possibilities of building smart specialisation strategies and industrial policies which are aligned with `high-road strategies'.
Keywords: O3; O31; O32; O33; 330; Clusters; ecological innovation; high road strategy; industrial policy; innovation policy; new technologies; post-industrialisation